The Senegalese paradox: fish and be fished - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
Bassirou Diarra, a fisheries inspector with the Office for Oceanography and Sea Fisheries (DOPM) in Senegal, writes to us about what he calls the Senegalese paradox : 'Here in our sub-region, our fisheries are in a catastrophic situation and it is...